Kisah Nabi Adam dan Hawa Prespektif Tafsir Al-Qurthubi - Nofi Pangastuti (At-Tafasir: Journal of Al-Qur'an Studies and Contextual Tafsir, 2024)
Abstract: The story of the Qur'an is a medium for conveying moral messages in the context of forming a people who have noble character. The stories in the Al-Qur'an are a method for realizing the goals you want to achieve. The stories in the Al-Qur'an are quite dominant, almost every letter is presented in the form of a story. However, the Koran is a book of religious preaching and stories as a method of conveying the material. There is a story in the Qur'an, the author chose the story of the Prophet Adam and Eve. What stands out about this story is that it has a different method compared to other literature, apart from that, Allah was so noble in ordering the angels and demons to bow down to Adam. For this reason, to make it easier for readers to learn the story, as a guide the author tells the story of Adam referring to Tafsir Al-Qurthubi. This type of research is library research or library research. Study in depth the verses of the Qur'an which discuss the story of the Prophet Adam and Eve which includes: How is Al-Qurthubi's method of interpreting the story of Adam and Eve in Tafsir Al-Qurthubi. What are the advantages, disadvantages and relevance of the story of Adam and Eve in Al-Quthubi's interpretation.The research method used is the thematic interpretation method of the figure Imam Al-Qurthubi. The theory in this research uses Sayyid Qutbh's story theory in which the story is divided according to the order of the first episode to the end. The advantages, disadvantages and relevance related to the story of Adam and Eve can help foster humanity's sense of devotion towards Allah SWT, forming moral values ”‹”‹with noble character. Keywords: Story, Characters,Relevance Abstrak: Kisah Al-Qur’an merupakan sebuah media penyampaian pesan-pesan moral dalam rangka pembentukan umat yang memiliki karakter yang mulia. Kisah-kisah dalam Al-Qur’an merupakan metode untuk mewujudkan tujuan yang ingin dicapai, kisah dalam Al-Qur’an cukup dominan, hampir setiap suratnya disajikan dalam bentuk kisah. Bagaimanapun juga Al-Qur’an kitab dakwah agama dan kisah-kisah sebagai metode penyampaian materinya. Adanya kisah dalam Al-Qur’an penulis memilih kisah Nabi Adam dan Hawa. Hal yang menonjol dari kisah ini yakni, memiliki metode yang berbeda jika dibandingkan sastra yang lain, selain itu sangking mulianya Allah memerintah para malaikat dan iblis untuk bersujud kepada Adam. Untuk itu agar pembaca lebih mudah dalam mempelajari kisah maka sebagai pedoman penulis menceritakan kisah Adam merujuk Tafsir Al- Qurthubi. Jenis penelitian ini adalah library research atau penelitian pustaka. Mengkaji secara mendalam tentang Ayat Al-Qur’an yang membahasa kisah Nabi Adam dan Hawa yang meliputi: Bagaimana metode penafsiran Al-Qurthubi tentang kisah Adam dan Hawa dalam Tafsir Al-Qurthubi. Bagaimana kelebihan, kekurangan, dan relevansi kisah Adam dan Hawa dalam tafsir Al-Quthubi. Metode penelitian yang digunakan yaitu menggunakan metode tafsir tematik tokoh Imam Al-Qurthubi. Teori dalam penelitian ini menggunakan teori kisah Sayyid Qutbh yang mana pembagian kisah sesuai dengan urutan episode pertama hingga akhir. Kelebihan, kekurangan dan relevansi terkait kisah Adam dan Hawa dapat membantu menumbuhkan rasa ketakwaan umat manusia terhadap Allah Swt, Membentuk nila-nilai moral dengan karakter yang mulia. Kata kunci: Kisah, Tokoh, Relevansi